Sending hidden data through WWW pages: detection and prevention Engineering - POLAK, L.; KOTULSKI, Z. (Engineering Transactions, 2010)
In the paper we propose a method of detecting and removing a hidden content which could be sent through the HTML code of WWW pages. We start from the overview of known methods of inserting hidden data to the mark-up languages (HTML or XML)-written texts. Next we propose a method of detecting suspicious web pages, based on statistical analysis. We also propose the method of transforming the HTML code of the web pages to remove any hidden communication.